Peran Keluarga Perokok dan ASI Eksklusif terhadap Stunting pada Balita di Pidie Jaya - Ully Fitria; Dian Rahayu; Freya Aprilia; Nuri Andriani; Sisca Amelia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stunting remains a major public health problem in Indonesia, particularly in Aceh Province. Family smoking behavior and adherence to exclusive breastfeeding are considered important determinants of child nutritional status. This study aimed to analyze the relationship between family smoking behavior and exclusive breastfeeding adherence with stunting among toddlers in Tuha Village, Trienggadeng District, Pidie Jaya Regency. This study used a quantitative cross-sectional design with a sample of 46 toddlers selected using simple random sampling. Data were collected through structured questionnaires and analyzed using univariate and bivariate analysis with logistic regression tests. The results showed that family smoking behavior was significantly associated with stunting (p = 0.002; OR = 0.12; 95% CI: 0.03–0.47). Meanwhile, exclusive breastfeeding adherence was not significantly associated with stunting (p = 0.940; OR = 0.94; 95% CI: 0.17–5.09). These findings indicate that exposure to cigarette smoke in the household is an important risk factor affecting child nutritional status. Strengthening family-based interventions, especially smoke-free home initiatives, is essential to reduce stunting prevalence.